2013
DOI: 10.1371/journal.pone.0085519
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast P5 Type ATPase, Spf1, Regulates Manganese Transport into the Endoplasmic Reticulum

Abstract: The endoplasmic reticulum (ER) is a large, multifunctional and essential organelle. Despite intense research, the function of more than a third of ER proteins remains unknown even in the well-studied model organism Saccharomyces cerevisiae. One such protein is Spf1, which is a highly conserved, ER localized, putative P-type ATPase. Deletion of SPF1 causes a wide variety of phenotypes including severe ER stress suggesting that this protein is essential for the normal function of the ER. The closest homologue of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 79 publications
2
74
0
2
Order By: Relevance
“…The levels of EP were slightly decreased by Mn 2ϩ , suggesting that Mn 2ϩ may substitute Ca 2ϩ with lower efficiency. However, we have previously found that Mn 2ϩ decreases Spf1p ATPase activity (18), a result that does not support the proposed role of Spf1p as a Mn 2ϩ transporter (28). The ATP dependence of the phosphorylation reaction indicates that Spf1p reacts with ATP with high affinity, as expected for the catalytic ATP site of a P-ATPase, and that it was not significantly changed by Ca 2ϩ .…”
Section: Effects Of Camentioning
confidence: 81%
“…The levels of EP were slightly decreased by Mn 2ϩ , suggesting that Mn 2ϩ may substitute Ca 2ϩ with lower efficiency. However, we have previously found that Mn 2ϩ decreases Spf1p ATPase activity (18), a result that does not support the proposed role of Spf1p as a Mn 2ϩ transporter (28). The ATP dependence of the phosphorylation reaction indicates that Spf1p reacts with ATP with high affinity, as expected for the catalytic ATP site of a P-ATPase, and that it was not significantly changed by Ca 2ϩ .…”
Section: Effects Of Camentioning
confidence: 81%
“…This data supports that PEMT pathway is also essential for mitochondrial function during ER stress and impairment of calcium. The defect of Pmr1p and Spf1p, implicated in protein glycosylation, influenced the conditions of ER stress stimulates LD formation in Saccharomyces cerevisiae (Fei et al 2009;Cohen et al 2013). Besides, the role of LD biogenesis and synthesis of TAG is a sign of cellular stress, and it was proposed that alterations in PC homeostasis might be the source of TAG (Al-Saffar et al 2002 andIorio et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Spf1 and Smf2 activities might be required for ER and Golgi manganese supply and thus be required for vesicle-mediated manganese transport. Recently, the Spf1 has been shown to regulate Mn 2ϩ transport into the ER (14), and the addition of extracellular Ca 2ϩ accordingly suppressed SPF1 mutant phenotypes (35,55). Smf2 was predicted to transport Mn 2ϩ across membranes toward the cytosol by the assumption that Nramp transporters transport divalent cations in this direction (8).…”
Section: Discussionmentioning
confidence: 99%
“…B, CaCl 2 fails to rescue CFW resistance of pmr1⌬ mutants in the absence of Spf1 or Smf2. Shown is CFW sensitivity of pmr1⌬ upon additional deletion of the low affinity Mn 2ϩ transporter PHO84 (12), the vesicular Mn 2ϩ transporter SMF2 (10), the vacuolar Ca 2ϩ /H ϩ exchanger VCX1 (68), the plasma membrane Ca 2ϩ channel CCH1 (69), the vacuolar Fe 2ϩ /Mn 2ϩ transporter CCC1 (19), and the putative ER Mn 2ϩ -transporter SPF1 (14). Drop test analysis of WT, pmr1⌬, pho84⌬, pmr1⌬ pho84⌬, smf2⌬, pmr1⌬ smf2⌬, vcx1⌬, pmr1⌬ vcx1, cch1, pmr1⌬ cch1⌬, ccc1⌬, pmr1⌬ccc1⌬, spf1⌬, and pmr1⌬ spf1⌬ cells is shown.…”
Section: Cacl 2 Counteracts Mnmentioning
confidence: 99%
See 1 more Smart Citation